The New Evangelization of the Catholic Church in the Context of Modern Socio-Cultural Changes - Turchyn, Yaryna; Zdoroveha, Mariana (Studia Warmińskie, 2020)
The article is dedicated to the analysis of new evangelization as a missionary activity of the Roman Catholic Church because of rapid development of Internet, digital devices and social media around the world. It has been determined main goal of new evangelization as drawing people back from the path of secularism to the Christianity. The author outlines five areas for spreading a new evangelization in the world, which are culture, social sphere, economy, civil society, science and technology. It has been analyzed an understanding, perception and main approaches of Catholic Pontiffs to the implementation of new evangelization in the world. The author analyses social networks and Internet highlighting most popular platforms where Catholic Church has many followers, which became an evidence of successful implementation of new evangelization. Among the challenges is it pointed out the necessity for Catholic Church remain both online and offline that requires more time for communication, particular digital knowledge for proclaiming the Gospel via social media as well as having digital devices that would help people connect with their church. The author draw conclusions, noting that further implementation of new evangelization of the church would be aimed at improving its efficiency, quality of presenting main values as well as ease of perception by target audience.